STRATEGI INOVASI PENDIDIKAN DI ERA DIGITAL: ANALISIS KUALITATIF FAKTOR PENGHAMBAT DAN PENDUKUNG DI LINGKUNGAN KAMPUS POLITEKNIK PENERBANGAN INDONESIA CURUG - Mushlih Aditya, Mokhamad Ilham; Lamtiar, Suse; Jati Utama, Risqi Wahyu; Anisa, Khairun; Sita Perwitasari, Ni Putu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The digital transformation of vocational higher education presents structural and cultural challenges, especially within institutions that apply a semi-military system such as the Indonesian Aviation Polytechnic (PPI) Curug. This study aims to identify the inhibiting and supporting factors influencing the implementation of digital education innovation strategies using a qualitative approach. Data were collected through semi-structured interviews with cadets and lecturers, and were complemented by relevant document analysis to ensure a comprehensive contextual understanding. The findings indicate that major barriers include limited digital infrastructure, misalignment between learning platforms and vocational needs, lack of technical training, and rigid organizational systems. Conversely, innovation is supported by individual lecturer initiatives, access to digital devices, active communication, and the informal adoption of blended learning. Analysis based on the Technology–Organization–Environment (TOE) framework reveals that successful digital innovation depends heavily on technological readiness, organizational support, and environmental compatibility. This study recommends a contextualized, participatory, and adaptive digitalization strategy tailored to the characteristics of vocational education and semi-military systems, along with institutional strengthening through training and evidence-based policy development.